INTEGRASI ICT DALAM PENDIDIKAN ISLAM Suatu Alternatif Pendekatan Pembelajaran Masa Depan - Promadi Promadi (MIQOT: Jurnal Ilmu-ilmu Keislaman, 2010)
Abstract: Integration of ICT in Islamic Education: An Alternative Approach of Future Learning The importance of the use of information and telecommunication technology in Islamic education is undeniable. The merit of the use of such kind of technology not only because it provides great number of up-to-date collection of information but more importantly this also makes it more accessible, faster and economical. The author traces the historical root of information and communication process in Islam and compares it to the emerging E-education in the last decades. It is argued that E-education will provide more room for optimum use of virtually equipped education facilities which is developing faster than ever predicted. The challenge for the future is that the integration of information and communication technology in Islamic education is not something to be avoided but rather an alternative learning approach which becomes a necessity in the competing professional educators.Kata Kunci: ICT, E-Learning, Virtual, Multimedia, PAIKEM, Consctructivism